(untitled) (Contemporary Journal of Social Science Review, 2025)
This study presents an analytical overview of Zartusht Nama by Munshi Muhammad Khalil-ur-Rahman, focusing on the life, teachings and religious thought of Zoroaster. Drawing upon primary sources such as the Avesta, Gatha, Pahlavi literature, and writings of Muslim historians, the book portrays Zoroaster as a historical religious reformer rather than a mythical figure. The study highlights that the core message of Zoroaster was based on monotheism, moral purification, social justice, and belief in the hereafter. Although the doctrine of dualism (good and evil) later became associated with Zoroastrianism, textual evidence from the Gathas suggests that Zoroaster himself upheld strict monotheism. The role of political patronage, particularly that of King Vishtaspa (Gushtasp), is identified as a decisive factor in the institutionalization and spread of Zoroastrianism in Iran and neighboring regions. Overall, the book provides a critical and historically grounded understanding of Zoroaster’s religious mission and its long-term impact on ancient civilizations.